Individualizacija kontrolja utomlenija pri zanjatijach fiziceskoj kul'turoj i sportom - Rozencov, V. V. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The purpose of this paper was to develop the method of the individual control of the degree of fatigue on dynamics of the change of the critical frequency of light flashings. The researches were carried out with the use of the velosimulator. The persons who were not engaged in the physical culture and sports, and also athletes of the various qualifications had taken part in the testing. The groups of examinees of different sex and age were consisted of 8 persons. The method of the individual control of fatigue consists of construction of the phase trajectory displaying dynamics of change of critical frequency of light flashings during the testing. The moment of the transition from the state of fatigue to the state of overwork was determined on time of change of the direction of the phase trajectory.